PERTUMBUHAN DAN HASIL CABAI BESAR (Capsicum annuum L.) YANG DIBERI PUPUK HAYATI PETROBIO PADA TANAH GAMBUT PEDALAMAN - Natalia, Natalia; Atikah, T. A.; Syahrudi, Syahrudi (AgriPeat, 2015)
The purpose of this study was to determine the effect of petrobio on soil biological inland peat on the growth and yield of chili. The design of experiments used Completely Randomized Design (CRD) single factor consisting of 6 treatments was: 0 kg ha-1 (control), 10 kg ha-1, 20 kg ha-1, 30 kg ha-1, 40 kg ha-1, 50 kg ha-1. The variables measured were: plant height, number of productive branches, number of fruits, fresh fruit weight, and the weight of dried fruit. The results showed that applying of dose of petrobio-fertilizers on peat soil had significant effect on plant height, number of productive branches and yield. Biological fertilizer of Petrobio 50 kg ha-1 was able to increase the average height plants, number of productive branches, crop yield, fresh weight of fruit and dry weight of fruit by 61.60 cm, 7.80, 16.20 fruit plant-1, 129.63 g plant-1, 23.26 g plant-1 respectively.